2010
DOI: 10.1002/jctb.2414
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of toluene and sulfur compounds removal by means of an integrated process involving the coupling of absorption and biodegradation

Abstract: International audienceBACKGROUND: Scrubbing using an organic solution instead of an aqueous solution could be a useful way to improve the removal of hydrophobic compounds. Absorption of toluene, dimethyldisulfide (DMDS) and dimethylsulfide (DMS) in an organic solution (di-2-ethylhexyladipate--DEHA), followed by biodegradation by activated sludge was considered, with particular attention to kinetic aspects. DEHA was selected for its relevance in terms of absorption capacity and absorption velocity of the select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…This result highlights the relevance of the NAP selection in order to implement TPPBs with a NAP highly affine for the target VOC. Thus, VOC-NAP pairs yielding is one of the most critical parameters in TPPB design [13,36,48,49]. The model also showed a high sensitivity towards a decrease in…”
Section: Sensitivity Analysismentioning
confidence: 90%
“…This result highlights the relevance of the NAP selection in order to implement TPPBs with a NAP highly affine for the target VOC. Thus, VOC-NAP pairs yielding is one of the most critical parameters in TPPB design [13,36,48,49]. The model also showed a high sensitivity towards a decrease in…”
Section: Sensitivity Analysismentioning
confidence: 90%
“…The value (H') obtained for pure DEHP was 0.99 Pa.m 3 .mole -1 . As a comparison, the value of the toluene partition coefficient in silicone oil (PDMS, 5 cP viscosity) and hexadecane given in the literature were 1.6 and 2.50 Pa.m 3 .mole -1 , respectively (Vuong et al, 2009;Darracq et al, 2010). Several volume ratios of DEHP in water were tested (5%, 2%, 0.5% and 0.1%).…”
Section: Methodsmentioning
confidence: 99%
“…However, NAPL can be attacked by microorganisms: for example (Darracq et al, 2009) found that DEHA was assimilated by activated sludge. Possible NAPL assimilation is especially undesired owing to their significant cost and hence their recycling is important in view of their reuse in a TPPB (Cesário et al, 1998;Darracq et al, 2010). Muñoz et al, (2007) considered that it is difficult to predict the stability of a given NAPL in the presence of microorganisms on long term, owing to a possible emergence of microorganisms able to degrade the NAPL.…”
Section: Introductionmentioning
confidence: 99%
“…The reducing load test was able to show the relationship between a declining free nitrous acid (FNA) concentration and the decreasing nitrite production. Darracq et al (2010) by Hafez et al (2010). It was found that the process achieved significant biomass yield reduction due to anoxic consumption of organic matter.…”
Section: Industrial Wastesmentioning
confidence: 99%